1998
DOI: 10.1002/(sici)1097-4547(19981015)54:2<169::aid-jnr5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human IP-10 gene expression in astrocytoma cells by inflammatory cytokines

Abstract: Because of its prominent expression in central nervous system inflammatory pathology by astrocytes, we examined the mechanism of human IP-10 (hIP-10) gene induction by interferon-gamma (IFN-gamma) and tumor necrosis factor-alpha (TNF-alpha) in astrocytoma cells. When present together, IFN-gamma and TNF-alpha induced robust accumulation of hIP-10 mRNA, but hIP-10 mRNA was minimally induced when astrocytoma cells were treated with individual cytokines. This pattern of expression resembled that previously describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 27 publications
2
45
0
Order By: Relevance
“…The promoter regions for both of these chemokines contain several transcription regulatory elements, but analysis of the IL-8 promoter has shown that expression requires the activity of a combination of either NF-B and AP-1 or NF-B and NF-IL-6 (Mahe et al, 1991;Yasumoto et al, 1992). Maximal IP-10 expression also requires cooperation between two sites, with strong promoter activity involving both an interferon-stimulated response element and an NF-B site that binds a p65 homodimer (Majumder et al, 1998). The fact that activation of astrocytes with nucleotides in the presence of IL-1␤ led to the differential regulation of IL-1␤-induced IL-8 and IP-10 expression was unexpected, and at the present time the mechanism for this remains unclear.…”
Section: Discussionmentioning
confidence: 80%
“…The promoter regions for both of these chemokines contain several transcription regulatory elements, but analysis of the IL-8 promoter has shown that expression requires the activity of a combination of either NF-B and AP-1 or NF-B and NF-IL-6 (Mahe et al, 1991;Yasumoto et al, 1992). Maximal IP-10 expression also requires cooperation between two sites, with strong promoter activity involving both an interferon-stimulated response element and an NF-B site that binds a p65 homodimer (Majumder et al, 1998). The fact that activation of astrocytes with nucleotides in the presence of IL-1␤ led to the differential regulation of IL-1␤-induced IL-8 and IP-10 expression was unexpected, and at the present time the mechanism for this remains unclear.…”
Section: Discussionmentioning
confidence: 80%
“…IFNgmediated induction of IP-10 can be seen in most IP-10-expressing cell types including monocytes/macrophages, although in dermal fibroblasts and astrocytoma cells, the induction is weak and TNFa or a combination of IFNg/TNFa are required. 21,40 The physiological relevance of this regulation is not yet understood, as local IFNg concentrations in adipose tissue have not been investigated. Given the fact that potentially IFNg-producing T cells have been found in epicardial tissue, 33 paracrine effects of IFNg-secreting immune cells on adipocytes seem conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…For EMSAs, where indicated, the cells were stimulated with IL-1␤ or TNF for 20 min. The NF-B binding site (5Ј-GAGCAGAGGGAAATTCCGTA-ACTT-3Ј) from the IFN-inducible protein 10 (IP-10) gene was used as a probe (44). Complementary oligonucleotides, endlabeled with polynucleotide kinase and ␥-32 P-labeled ATP, were annealed by slow cooling.…”
Section: Cell Line For Mutagenesis and Generation Of Constitutive Mutmentioning
confidence: 99%